Preoperative Atrial Fibrillation is associated with long‐term morTality in patients undergoing suRgical AortiC valvE Replacement. Issue 10 (26th July 2021) - Farag, Mohamed; Kiberu, Yusuf; Ashwin Reddy, S.; Shoaib, Ahmad; Egred, Mohaned; Krishnan, Unni; Fares, Mina; Peverelli, Marta; Gorog, Diana A; Elmahdy, Walid; Berman, Marius; Osman, Mohamed; et al.
Abstract: Introduction: Atrial fibrillation (AF) is frequent after any cardiac surgery, but evidence suggests it may have no significant impact on survival if sinus rhythm (SR) is effectively restored early after the onset of the arrhythmia. In contrast, management of preoperative AF is often overlooked during or after cardiac surgery despite several proposed protocols. This study sought to evaluate the impact of preoperative AF on mortality in patients undergoing isolated surgical aortic valve replacement (AVR). Methods: We performed a retrospective, single‐center study involving 2628 consecutive patients undergoing elective, primary isolated surgical AVR from 2008 to 2018. A total of 268/2628 patients (10.1%) exhibited AF before surgery. The effect of preoperative AF on mortality was evaluated with univariate and multivariate analyses. Results: Short‐term mortality was 0.8% and was not different between preoperative AF and SR cohorts. Preoperative AF was highly predictive of long‐term mortality (median follow‐up of 4 years [Q1–Q3 2–7]; hazard ratio [HR]: 2.24, 95% confidence interval [CI]: 1.79–2.79, p  < .001), and remained strongly and independently predictive after adjustment for other risk factors (HR: 1.54, 95% CI: 1.21–1.96, p  < .001) compared with preoperative SR. In propensity score‐matched analysis, the adjusted mortality risk was higher in the AF cohort (OR: 1.47, 95% CI: 1.04–1.99, p  = .03) compared with the SR cohort. Conclusions: Preoperative AF was independently predictive of long‐term mortality in patients undergoing isolated surgical AVR. It remains to be seen whether concomitant surgery or other preoperative measures to correct AF may impact long‐term survival.